Successful multimodal treatment of intraoral salivary duct carcinoma in a patient with multiple lymph node metastases: a case report. Issue 1 (December 2017) - Imaue, Shuichi; Tomihara, Kei; Hamashima, Takeru; Tomizawa, Gakuto; Nomura, Kuninori; Sasahara, Masakiyo; Noguchi, Makoto
Abstract Background Salivary duct carcinoma (SDC) is a high-grade salivary gland malignancy that is associated with an aggressive clinical behavior and poor prognosis. Herein, we report on a long surviving case of SDC of the minor salivary gland with multiple lymph node metastases (LNMs). Case presentation An 83-year-old woman presented with a history of lymphadenopathy in the right side of the neck and recent onset and rapid growth of a mass in the right buccal region. Clinical examinations and biopsy findings were suggestive of a salivary gland malignant tumor with regional LNMs. The patient was treated with neoadjuvant chemotherapy. Tumor excision and ipsilateral radical neck dissection were performed, followed by adjuvant chemoradiotherapy. Postoperative histological examination revealed a tumor with irregular nests of atypical ductal epithelial cells, a cribriform growth pattern, and comedo-like central necrosis that lead to a final diagnosis of SDC. LNMs were observed in six lymph nodes of the right side of the neck. The patient underwent postoperative chemotherapy using single-agent cisplatin that was administered concurrently with radiotherapy (total, 65 Gy). There was no evidence of local recurrence or distant metastasis for >6 years. Conclusions Although available data on treatment modalities for SDC remain limited, multimodal therapy may contribute to improved clinical outcomes in patients with advanced intraoral SDC.